In Lens of the Odd: Constructing the Otherness in Malaysian History The Role of Financial Development and Manufacturing Sector Expansion on Emission Reduction for Sustainable Economic Development in the World’s Biggest Emitter Asia - Norena Abdul Karim Zamri, Adam Abdul Karim Zamri (International Journal of Advanced Science and Technology, 2020)
This study provides an understanding of Otherness concept in contemporary social and cultural thought. It tries to delves on the many histories consumed by the Malaysian publics. It is based on the premised that historical knowledge of the nation is ethnicized. This study is aware that there is no official history of the nation. What has come to be known as the nation’s history evolved over space and has been accepted currently as mainstream history. By combining the fields of postcolonial theory and culture studies, it uses a theoretical framework that attaches contemporary cultural debates regarding the representation discourse with the colonial stereotypes and racialized imageries. Through the application of qualitative content analysis and quantitative analysis, the study strives to make a theoretical contribution and adding to the body of the knowledge. This study deduce with a review of different types of racial otherness in Sarawak, by highlighting Orientalism as a form of persistent that has been maintained by colonial binaries throughout the history of Malaysia.